Global tide variables - Obst, Matthias (University of Gothenburg, 2017)
This dataset contains global tidal variables in form of GeoTIFF raster layers generated by Vestbo et al (2018). The raster layers were generated using the Finite Element Solution oceanographic model (FES2012), provided by Noveltis, Legos and CLS Space Oceanography Division and distributed by AVISO+ (http://www.aviso.altimetry.fr). FES2012 includes overall 32 tidal constituents distributed on 1/16° grids (amplitude and phase), corresponding to 3.75 arc-minutes.

The dataset contains the following five raster layers, plus the algorithm for calling the FES program (written in C).

(1) Annual average cycle amplitude in cm.
(2) Maximum annual cycle amplitude in cm.
(3) Annual standard deviation of cycle amplitude in cm.
(4) Annual average duration of tidal cycles in hours.
(5) Annual number of cycles.

A detailed description of the data generation procedure is provided in the original paper (Vestbo et al 2018).
References: Vestbo S, Obst M, Quevedo-Fernandez F, Intanai I, Funch P (2018). Present and Potential Future Distributions of Asian Horseshoe Crabs Determine Areas for Conservation. Frontiers in Marine Science. doi: 10.3389/fmars.2018.00164 https://www.frontiersin.org/articles/10.3389/fmars.2018.00164/abstract

The dataset contains the following five raster layers, plus the algorithm for calling the FES program (written in C):
(1) Annual average cycle amplitude in cm
(2) Maximum annual cycle amplitude in cm
(3) Annual standard deviation of cycle amplitude in cm
(4) Annual average duration of tidal cycles in hours
(5) Annual number of cycles

Data med globala tidvattenvariabler i form av GeoTIFF rasterlager genererade av Vestbo et al (2018).

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0243

The dataset contains the following five raster layers, plus the algorithm for calling the FES program (written in C):
(1) Annual average cycle amplitude in cm
(2) Maximum annual cycle amplitude in cm
(3) Annual standard deviation of cycle amplitude in cm
(4) Annual average duration of tidal cycles in hours
(5) Annual number of cycles
Globala tidvattenvariabler - Globala tidvattensvariabler
Keywords: OCEANS; TIDAL COMPONENTS; TIDAL HEIGHT; TIDAL RANGE; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Oceans; Kust och hav; Environment; Miljö